Gandhi x-rayed - Sharma, Raghav Sharan (New Delhi Manas Publications, 2021)
Is there some value to the legacy of Mohandas Karamchand Gandhi (Mahatma Gandhi) in the twenty-first century? Do his philosophy and practices have any relevance today? He has been widely advertised and remained controversial in his lifetime and still remains so. In this book, we will try to search all these aspects including his weakness for women, his theory of brahmacharya, his role in the partition of India and all the myths that were deliberately woven around him by a group of people for their own benefit disregarding our motherland India. Gandhi was a complex, full of contradictions and opposites character. The question is how to understand Gandhi who is hidden (3z(Bbehind the mask of Mahatma(3y(B. To begin, we will take a closer look at the propaganda machine of Gandhi erected by Miss Slade (Mirabehn), Ghanshyam Das Birla, Dalmia, Jamnalal Bajaj, Amba Lal, and Britishers. We should unveil his participation in Zulu War, Boer War and First World War in favour of the British and assess the intent and content of his non-violence and denial of science, his passive loyalist satyagraha and his tactical racism. His under-pragmatic and hidden facets need to be explored. Ambedkar called his politics hollow and noisy. Subhas Chandra Bose recognized him as a loyalist and compromiser with the British Raj. Veer Savarkar assailed him for his so-called Ahimsa, absolutism, his fetish for goat$1 (Bs milk, and charkha.s
Keywords: Politics and government